KORELASI ANTARA HASIL TES MIKROSKOPIS DENGAN TES CEPAT MOLEKULER PADA PASIEN TUBERCULOSIS DAN MULTIDRUG RESISTEN TUBERCULOSIS DI RSUD Dr. H CHASAN BOESOIRIE TERNATE - Andi Sitti Nur Afiah; fera the (Kieraha Medical Journal, 2020)
Tuberculosis (TB) is a pulmonary disease caused by Mycobacterium tuberculosis. Globally in 2018 theestimated number of people affected by TB was estimated at 10.0 million population and 484,000 cases ofmultidrug-resistant TB (MDR-TB). This study aims to determine the correlation between microscopic testresults with RMT on TB and MDR-TB patients at RSUD Dr. H Chasan Boesoirie Ternate. This type of researchis analytical research using a retrospective approach. The sample in this study were patients with suspected TBand MDR-TB who had performed microscopic tests and TCM in February – April at 2020 in the ClinicalPathology Laboratory of RSUD Dr. H Chasan Boesoirie Ternate, who met the inclusion and exclusion criteria.Data were analyzed using the SPSS program analysis was carried out in stages, namely by univariate andbivariate using chi-square test. From 100 samples, the results of RMT examination with TB suspects were 30rifampicin sensitive samples with 2 rifampicin resistance and 5 rifampin sensitive samples for TB MDR-TBsuspects RMT examination results. Chi-square test results obtained the value of p = 000 (p <0.05). There is stilla significant difference between the microscopic test results with RMT in TB and MDR-TB suspect patients atRSUD Dr. H Chasan Boesoirie Ternate.